A design approach for a distributed system to handle Chinese - Clark, James L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
In designing systems to handle non-Roman alphabet languages, unique problems in information retrieval are encountered. The concept of "P-trees” will be explained and compared to B-trees. Experiences in applying P-trees to non-Roman alphabet retrieval environments will be covered in detail.